SP0166 Long-term outcome of jia into adulthood. (15th June 2017) - Flato, B
Abstract : Background: In patients with juvenile idiopathic arthritis (JIA), scarce information on disease outcomes into adulthood are available. Objectives: To review the long-term outcome and possible time trends in adult JIA and discuss how JIA in adulthood is similar to or different from adult onset rheumatic diseases. Results: JIA is a heterogeneous group of diseases, but across different categories patients with JIA share some clinical, prognostic and genetic characteristics different from those found in adult onset arthritis (i.e. growth disturbances, more varying prognoses, and HLA-DRB1*08). The most common categories of JIA, oligoarthritis and RF-negative polyarthritis, do not have any adult counterpart. On the other hand, 82–96% of patients with systemic, RF-positive polyarticular, psoriasis related, and enthesitis related JIA were recently found to fulfil the criteria for adult Stills, RA, psoriatic arthritis, and adult spondylarthropathy, respectively. Furhermore, recent analyses of large patient groups show that patients with oligoarticular and RF-negative polyarticular JIA share HLA associations with seronegative RA (HLA-DRB1 amino acid at position 13). At transition to adult care, about half of the JIA patients (range 42–67%) have active disease or are on anti-rheumatic medication. In adult JIA patients, active disease after more than 20 years of disease duration occured in 40 percent (range 37–43%). Differences in definitions of remission, classification criteria and/or selection of patient may explain these variations. Within a cohort, no reduction were found in the proportion of patients with active JIA from childhood to adulthood in 3 long-term longitudinal studies; 62% at 5- and 60% at 17-year followup, 42% at 10- and 37% at 26-year followup) and 45% at 15- and 41% at 30-year followup. Limitation in physical functioning has been found in 45–50% of adult JIA patients. The proportion with severe disability has increased with increased disease duration in several cross sectional and one longitudinal study. However, no definite trends towards detoriation of physical functioning over time were found in two recent longitudinal studies. The proportion of JIA patients with severe disability was low in long-term studies from this century, 3% to 11%, compared to 15–48% in studies from 1960 to 1990. Up to 90% of the patients with childhood polyarthritis had radiographic damage in studies from 1966–76, compared to about 40% in studies from this century. In the total group of JIA patients, 24%>36% developed erosive disease, most frequently in wrists and hips. However, the use of radiographic scoring systems in JIA has been hindered by growth disturbances and varying joint distributions. Thus radiographic progression has never been investigated in clinical trials. Several studies have shown that adults with JIA experience more pain, poorer health related quality of life and lower employment rates than age and sex matched controls from the general population, in spite of similar or higher education levels. A new study shows that JIA has a detrimental effect on HRQOL both in patients with and without clinical remission, and physical, but not mental, HRQOL deteriorate slightly from adolescence to adult life. Ongoing active uveitis into adulthood has been found in half of the patients with JIA associated uveitis. One third of them have visual impairment and 40% need ocular surgery in early adult life. Recent studies indicate that adult JIA patients have increased rates of subclinical atherosclerosis and malignancies. The use of arthroplasties in JIA patients decreased dramatically from 1990 to 2005, while the rates were stable in RA and increased in spondylarthropathy and osteoarthritis patients. Joint surgery now occurs in less than 15% of adult JIA patients. Previous long-term followup studies have mainly been performed before biologic agents were available or early methotrexate was used. Long-term outcomes in JIA patients treated with biologic agents have been described in two registry based studies. Inactive disease was achieved in 24–67% of the adult JIA patients and 52–74% were still on a biologic agent at last followup. It has been found that biologics improve physical HRQOL in children with JIA, and that most of the acquired improvement is maintained in adult life. However, biologics were started several years after disease onset in these studies. Only 38–56% of adult JIA patients with long-term active disease were on synthetic or biological DMARDs according to recent followup studies. Conclusion: About half of JIA patients have active disease into adulthood. JIA affects physical outcome, HRQOL and visual outcome, but adult patients with long-term active JIA seems to receive inadequate therapy. So far, the long-term outcome in patients receiving early biologic and/or synthetic DMARDs is not known. Disclosure of Interest: None declared